2015
DOI: 10.4314/ajtcam.v11i6.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-harvest methyl jasmonate treatment on post-harvest fruit quality of Japanese plums

Abstract: Background: Plum fruits constitute a good source of natural antioxidant substances. Particularly, plums contain large amounts of phenolic compounds and flavonoids having natural antioxidant activity which is effective in human diet. The aim of this study was to evaluate the effects of pre-harvest MeJA treatment on the fruit quality and bioactive compounds of three different Japanese plums under storage conditions. Materials and Methods: The effects of pre-harvest methyl jasmonate treatment (MeJA) on weight los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
6
5
0
Order By: Relevance
“…These results are agreed with those obtained by Kucuker and Ozturk (2014) cold storage. They reported that, methyl jasmonate treatment decreased plum fruit weight loss than the control through the cold storage.…”
Section: Fruit Weight Losssupporting
confidence: 92%
“…These results are agreed with those obtained by Kucuker and Ozturk (2014) cold storage. They reported that, methyl jasmonate treatment decreased plum fruit weight loss than the control through the cold storage.…”
Section: Fruit Weight Losssupporting
confidence: 92%
“…The high firmness of SA treatment fruit may be explained by the fact that SA may induce a high acquired resistance in plants, which to a vital factor in limiting the injurious effects of abiotic stresses and inhibiting water loss from fruits. these results are in accordance with those of Ahmad et al (2013) in their work on sweet orange with concentrations of 2, 4, 6, and 8 mm of ascorbic acid and in which the lower concentration 2 mm gave the second highest firmness values of fruit which corroborate the values of fruit firmness related to JO treatment are supported by the similar results obtained by Kucuker and Ozturk (2014) reporting that Jasmonate treated trees of Prunus salicina (plums) resulted in higher yields and increasing fruit firmness.…”
Section: Physical Characteristicssupporting
confidence: 91%
“…Foliar sprays SA on Valencia trees had significantly increased yield, fruit weight, and reducing drop %, owing to salicylic acid effect in enhancing metabolism of plants and biosynthesis during fruit development (Habasy, 2015). Kucuker and Ozturk (2014) cited that preharvest applying methyl Jasmonate on Japanese plums had resulted in higher yield because of its regulatory role in fruit growth and ripening. Foliar application of JO as reported by Iqbal et al (2012) increased fruit weight and this effect is due to enhancing resistance against pests and citrus green and blue molds on tree and that lead to reinvigorating leaves so that photosynthesis will be kept in high rates.…”
Section: Resultsmentioning
confidence: 99%
“…However, contrary effects have been reported; raspberries treated with MJ showed higher SS, total sugar, fructose, glucose, sucrose, malic and citric acid contents than untreated fruit (Wang and Zheng 2005). In plums, Kucuker and Ozturk (2014) reported that the MJ-treated fruit had higher pulp firmness.…”
Section: Resultsmentioning
confidence: 76%
“…The effects of exogenous MJ on fruit ripening are not clear yet and are dependent on the species, cultivars, and physiological stage of the fruit (Fan et al 1997;Khan and Singh 2007;Ziosi et al 2008;Kucuker and Ozturk 2014).…”
Section: Resultsmentioning
confidence: 99%